FILOSOFI PENDIDIKAN TORAJA DAN PENDIDIKAN PRAMODERN DI TORAJA - Anpriga Anpriga; Kliver Daniel Kapang, Helcha Srianti Kaissanan, Firka Limbong Lempan, Reiga Saputri (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
Education in Toraja reflects harmony between traditional cultural values and the modern education system. This combination allows strengthening cultural identity through the application of traditional values in formal learning. Traditional educational approaches rich in local wisdom can be integrated into the curriculum through contextual methods and holistic character education programs. By utilizing the strengths of these two approaches, the education system in Toraja has the potential to create a generation that is not only intellectually superior but also has wise morals and a strong cultural identity. This education is a means of transformation to produce a society that is relevant to the needs of the times without losing its cultural roots. The synergy between tradition and modernity makes education in Toraja an inspiring model in developing a meaningful and holistic education system for the future